2017
DOI: 10.1142/s0217751x17501433
|View full text |Cite
|
Sign up to set email alerts
|

Quantum speed limit for a relativistic electron in the noncommutative phase space

Abstract: The influence of the noncommutativity on the average speed of a relativistic electron interacting with a uniform magnetic field within the minimum evolution time is investigated. We find that it is possible for the wave packet of the electron to travel faster than the speed of light in vacuum because of the noncommutativity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…First, the critical speed, which the particle can not overcome during its evolution in gravitational field, can be more than the speed of light. The same observation has been made from analysis of MPTD particle in specific metrics [49][50][51][52][53]. Second, the longitudinal acceleration grows up to infinity in the ultrarelativistic limit.…”
Section: Advances In Mathematical Physicssupporting
confidence: 59%
“…First, the critical speed, which the particle can not overcome during its evolution in gravitational field, can be more than the speed of light. The same observation has been made from analysis of MPTD particle in specific metrics [49][50][51][52][53]. Second, the longitudinal acceleration grows up to infinity in the ultrarelativistic limit.…”
Section: Advances In Mathematical Physicssupporting
confidence: 59%
“…Such a model was originally proposed to address the infinity problem in quantum field theory [1,2] and was shown later that similar property can also appear in both string theory embedded in a background magnetic field [3] and quantum gravity [4]. It has been shown that the rotational symmetry can be broken [5,6], and consequently the energy levels of hydrogen atom [7] and Rydberg atoms [8] and topological phase effects [9][10][11] as well as the quantum speed of relativistic charged particles [12][13][14][15] and fluid [16] can receive interesting corrections. Algebra (1) can be accomplished by a replacement → + /(2ℏ).…”
Section: Introductionmentioning
confidence: 95%
“…In [44], the authors study the noncommutative (both the coordinates and momenta are noncommutative simultaneously) Dirac equation. They find that Lorentz invariance will be violated in noncommutative Dirac equation since the average speed of an electron wave packet exceeds the speed of light in vacuum if the magnetic field is strong enough.…”
Section: Introductionmentioning
confidence: 99%